Thinking Tools: navigating a 3-year PhD journey - Ibrahim, Rahinah (Partridge Publishing, 2020)
The Thinking Tools is a self-help book for preparing doctoral students towards navigating a 3-year PhD journey. It will help new doctoral candidates who just realized how overwhelming things are once the journey started. It also enlightens those doctoral students who are thinking about quitting the journey because the end never seems to be in sight. Based on the author's ethnography study, the book points out key misconceptions at different research design phases, which are detrimental to postgraduates from developing countries due to differences in their learning cultures. The book includes several unconventional tips such as for fast critical writing and avoidance of research methodology thinking until after completion of rigorous literature review. The Thinking Tools book is a systematic compilation of selected simple tools for helping graduate students develop their understanding about the complex doctoral study. Kicking off with an emotional problem identification, the author introduces the innovative RQ Constructs formulae for developing novel inquiries. She details how this inquiry concept helps visualise the critical linkages among key research methodology components to ensure a doctoral qualification. The tools have proven to accelerate critical thinking competency if followed well by the doctoral students with some guidance from their supervisors.